PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP KELENGKAPAN PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2010-2012 - Vera Indrayani; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the influence of firm characteristics on the completeness of voluntary disclosure in annual reports of listed manufacturing companies in Indonesia Stock Exchanges in 2010 until 2012. Characteristics of the companies represented by tree independent variables and the completeness of voluntary disclosures as the dependent variables. Data from this study were obtained from financial statements and annual reports of manufacturing firms drawn from the Indonesia Stock Exchange and Indonesia Capital Market Directory. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange during the years 2010-2012 amounting to 158 companies and samples 74 companies. Determination of the sample using purposive sampling method. Type of data are secondary data in the form of annual reports as the media manufacturing companies. Data analysis tool is multiple regression analysis with the computer program SPSS version 17.The result of this study indicate that liquidity ratios, leverage ratios and profitability ratios, have a significant effect on the completeness of voluntary disclosures in annual reports of manufacturing companies collectively. Partially, only profitability ratios and leverage ratio of the company that has a positive influence on the completeness of voluntary disclosures in annual reports of manufacturing companies